Domain decomposition method with hybrid approximations applied to solve problems of elasticity - Grigorenko, A. Ya; Dyyak, I. I.; Prokopyshin, I. I. (International applied mechanics, 2008)
To solve two-dimensional boundary-value problems of elasticity, two iteration algorithms of the domain decomposition method are proposed: parallel Neumann–Neumann and sequential Dirichlet–Neumann. They are based on the hybrid boundary–finite-element approximations. The algorithms are proved to converge. The optimal parameters are selected using the minimum-residual and steepest-descent methods. Some plane problems of elasticity are solved as examples, and stationary and nonstationary iteration algorithms in these examples are analyzed for efficiency